ANLISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEBERHASILAN PENGAJUAN KREDIT USAHA RAKYAT DI BANK TABUNGAN NEGARA KANTOR CABANG MAGELANG - Malazia, Syahrul; Musthafa, Afif (Journal Accounting International Mount Hope, 2025)
Bank Tabungan Negara KC Magelang is a State-Owned Enterprise engaged in banking and financial business. People's Business Credit product is one of the business activities of Bank Tabungan Negara KC Magelang which is intended for business actors who want to develop their business. This study aims to determine the system and procedures applied by Bank Tabungan Negara KC Magelang in the People's Business Credit product. The study uses a qualitative approach and comprehensive data analysis regarding a problem. The sources of this research are primary data and secondary data obtained from the results of observations, interviews and documentation. The results of this study formulate conclusions about the People's Business Credit System and Procedures applied at Bank Tabungan Negara, obstacles in the implementation of People's Business Credit, namely many files are rejected by the UMKM processing center unit (SPU)/risk analyst because the submitted files do not meet the requirements, as well as efforts and solutions obtained in dealing with the many rejected files